Provision of health /disease screening and medication monitoring /management in New Zealand community pharmacies. (December 2014) - Zolezzi, Monica; Bye, Lynne; Harrison, Jeff; Tsuyuki, Ross T.; Shaw, John P.
ABSTRACT: Background: Access to health /disease screening (HDS) and medication monitoring /management (MM) services in New Zealand has traditionally been through general practitioners. While government and professional organisations are supportive of greater community pharmacy involvement, there has been little research on the extent of current provision or of the views of community pharmacists in this area. Aim: To describe the characteristics and extent of HDS and MM services provided in New Zealand community pharmacies, and to document pharmacists' opinions and perceived barriers in regard to the provision of these services. Methods: A four‐part questionnaire was developed to record: the types of HDS /MM services offered by community pharmacies; the opinions of respondent pharmacists regarding these services; the characteristics of community pharmacies offering the services; and the profiles of the respondent pharmacists. The questionnaire was distributed to 879 community pharmacies in New Zealand. Results: There were 458 valid questionnaires returned, with a response rate of 52%. Over half (59%) of the responding pharmacies reported provision of HDS and /or MM services, although there were relatively few 'high level' services such as cardiovascular risk assessment and disease management. Most services were paid for by pharmacy customers, although some District Health Boards paid for services such as Medicines Use Review. Pharmacists cited lack of remuneration, lack of time and limited access to patient information as the main barriers to greater involvement. Conclusion: At the time of this study (2007), community pharmacists in New Zealand were in the 'early adoption' phase concerning the provision of HDS and MM services.